Just Boys: Notes On The Novel Quarto Aberto, , By Tobias Carvalho - Silva, Claudimar Pereira [UNESP] (Univ Fed Minas Gerais, Fac Letras, 2024)
This article makes some appointments on Quarto aberto, , the debut generational novel by the young writer Tobias Carvalho, one of the most important voices in contemporary Brazilian literature at the end of the second decade of 2000s. The novel narrates the reunion of Artur, a younggay gay man from Porto Alegre, who does sporadic work as a drag queen, , with Eric, a boy with whom he had previously had a relationship. Artur lives in an open relationship with Ca & iacute;que, while Eric is also in a non-monogamous relationship with Ant & ocirc;nio. Soon, Ca & iacute;que and Ant & ocirc;nio are also engulfed in this intrincate net ofgay gay male desires, largely mediated by the technology of dating apps. Thus, based on the theoretical assumptions of Schollhammer (2012), Miskolci (2017) and Vasallo (2022), we intend to analyse Quarto aberto (2023), in the way this novel fictionalizes new possibilities of relationships, dissidents from the monogamous system, the movement ofgay gay men through large cities in search of sexual partners, and the relationship difficulties in early adulthood.
Keywords: Non-monogamy; male homoeroticism; dating apps; contemporary Brazilian literature; Tobias Carvalho